Life satisfaction, household income and personality theory - Eugenio Proto; Aldo Rustichini (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
We show that personality traits mediate the e ect of income on Life Satisfaction. The e ect is strong in the case of Neuroticism, which measures the sensitivity to threat and punishment, in both the British Household Panel Survey and the German Socioeconomic Panel. Neuroticism increases the usually observed concavity of the relationship: Individuals with higher Neuroticism score enjoy income more than those with lower score if they are poorer and enjoy income less if they are richer. When the interaction between income and neuroticism is introduced, income does not have signi cant e ect on his own. To interpret the results, we present a simple model where we assume that (i) Life Satisfaction is dependent from the gap between aspired and realized income, and this is modulated by Neuroticism and (ii) income increases in aspirations with a slope less than unity, so that the gap between aspired and realized income increase with aspirations. From the estimation of this model we argue that poorer tend to overshoot in their aspiration, while rich tend to under-shoot. The estimation of the model also shows substantial effect of traits on income.
Keywords: D03; D87; C33; 330; life satisfaction; household income; personality theory; neuroticism